PENGARUH PERAN APARAT PENGAWAS INTERNAL PEMERINTAH, PERAN LEGISLATIF DAN PARTISIPASI MASYARAKAT TERHADAP GOOD GOVERNANCE DI PEMERINTAH KOTA PEKANBARU (STUDI EMPIRIS PADA PEMERINTAH KOTA PEKANBARU) - Muhammad, Luthfi; Aunurrafiq, Aunurrafiq; Raja, Surya Adri Satriawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine and analyze the influence of the role of the government's internal supervisory apparatus, the role of the legislature, and community participation on Good Governance in the government of Pekanbaru City. This type of research is qualitative research with primary data. The population in the Pekanbaru City Government OPD with the sample selection used the purposive sampling method and the sample used was 93 respondents. The analytical method of this study used multiple linear regression with the SPSS 25 program. The results of the study concluded that the role of the government's internal supervisory apparatus, the role of the legislature, and community participation have a positive and significant effect on good governance. Keywords: The Role of the Government's Internal Supervisory Apparatus, Legislative Role, community participation, good governance